A novel sandwich structure ACF/CC@FeOCl as bifunctional cathode for efficient mineralization of trimethoprim in the heterogeneous electro‐Fenton process over a wide pH range. Issue 12 (6th August 2022) - Song, Yongjun; Wang, Aimin; Ren, Songyu; Zhang, Yanyu; Wen, Zhenjun; Zhang, Zhongguo
Abstract: BACKGROUND: It would be highly advantageous to develop a heterogeneous electro‐Fenton (HEF) system in which the catalyst is fixed to recycle easily and the electrode itself can produce and activate H2 O2 simultaneously. In this study, a new sandwich‐like bifunctional cathode using carbon cloth (CC) loaded with FeOCl nanoparticles and activated carbon fiber (ACF) was fabricated and used in the HEF process for the degradation of antibiotic trimethoprim (TMP). RESULTS: Experimental results showed that the activated carbon fiber and FeOCl‐modified carbon cloth cathode (ACF/CC@FeOCl) exhibited a promising catalytic performance to reduce O2 to generate H2 O2 on the surface of ACF and activate H2 O2 to generate hydroxyl radicals ( OH) at the active sites of FeOCl nanoparticles, thus enabling a rapid TMP degradation in a wide pH range (3–9). Various influencing factors, such as applied cathodic current, pH and TMP concentration, were investigated, and the optimal condition was found at 0.36 A, pH 3.0, and 100 mg L −1 TMP, where 99.7% TMP was degraded within 90 min and 74.4% total organic carbon (TOC) was removed within 360 min. Under the condition of 0.36 A and initial pH 6.8, 100 mg L −1 TMP was completely degraded within 120 min and the mineralization efficiency could achieve 61.5% within 360 min. The coumarin fluorescence probing technique and radical quenching experiments revealed that OH was the predominant reactive oxygen species (ROS) in the ACF/CC@FeOCl‐HEF process. CONCLUSION: The reusability and stability tests showed that the ACF/CC@FeOCl cathode has excellent performance and good stability, and this is very promising for the efficient degradation of refractory organic pollutants in the HEF process. © 2022 Society of Chemical Industry (SCI).